Viral Infection and Oral Habits as Risk Factors for Oral Squamous Cell Carcinoma in Yemen: A Case-Control Study - Nasher, Akram T.; Al-Hebshi, Nezar N.; Al-Moayad, Ebtisam E.; Suleiman, Ahmed M. (Elsevier, 2014)
Objective The role of qat chewing, tobacco (shammah) dipping, smoking, alcohol drinking, and oral viral infection as risk factors for oral squamous cell carcinoma (OSCC) in Yemen was assessed. Study Design A total of 60 cases of OSCC and 120 age- and gender-matched controls were analyzed with respect to demographic data, history of oral habits, and the presence of human papillomavirus (HPV)-16, HPV-18, or Epstein-Barr virus (EBV) as determined by Taqman quantitative polymerase chain reaction. Logistic regression analysis was used to identify independent predictors of the disease. Results Shammah use was the only risk factor for OSCC, with an odds ratio of 12.6 (CI, 3.3-48.2) and 39 (CI, 14-105) for the ex-users and current users, respectively. The association of shammah use alone with OSCC exceeded that of shammah use in combination with qat chewing, smoking, or both. EBV infection, smoking, and qat chewing showed no association with OSCC, while neither HPV-16 nor HPV-18 were detected in any sample. Conclusions Shammah use is a major risk factor for oral cancer in Yemen.